Front Langkan Sebagai Garis Pertahanan Pada Masa Revolusi Fisik di Sumatra Selatan Tahun 1947 - Pratama, Riski; Chairunnisa, Eva Dina; Suriadi, Aan (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The Langkan Front is the defense line of the Republic of Indonesia Army, South Sumatra Sub-Commandment on the left front which was formed after the physical revolution broke out in South Sumatra in 1947 or what is known as the five days and five nights war in the city of Palembang, this of course had an impact on the areas around the city Palembang. The purpose of this research was to find out the relationship (continuity) after the five days and five nights of war in Palembang with the front ledge incident at Banjoeasin en Kubustrekken, as well as what factors influenced and had an impact on this historic event. We hope that this research can be used as a basis for structural thinking based on scientific data, especially for the people of Kab. Banyuasin so that together we can increase our knowledge of regional history (local wisdom). The research method used is qualitative with a combined historical and library research approach. From the results of the research carried out, there is a value of historical causality (connectedness), between national events and their developments in the regions, especially in South Sumatra. And this research also analyzes the factors supporting the ledge front event, such as the geographical appearance of the region and the socio-cultural conditions of the community. So that later the historical facts that are formed can be used as a source of historical learning and can strengthen a sense of nationalism through a regional historical approach.